Composition
By reducing pressure and pressurized acetylation of the wood powder, acetylated wood powder without catalyst residue was prepared and thermoformed, which solved the problems of poor thermoformability and large environmental load of wood biomass molding materials, and achieved excellent thermoplasticity and mechanical properties.
Patent Information
- Application Number
- CN202380066100.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-16
- Filing Date
- 2023-09-14
- Publication Date
- 2025-04-25
AI Technical Summary
When using wood biomass as molding materials, the prior art has problems such as poor thermoformability and large environmental load, and the catalyst residue will cause the quality of the molded product to decline.
By subjecting the wood powder to a reduced pressure and pressurized acetylation treatment, acetylated wood powder without catalyst residue was prepared, and thermoformed under an inert gas atmosphere to form a composition with excellent thermoplasticity and mechanical properties.
The high thermoplasticity and excellent mechanical properties of wood biomass molding materials are achieved, which avoids the quality reduction caused by catalyst residues and reduces the environmental load.
Smart Images

Figure CN119894986A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a composition. In particular, the present disclosure relates to a composition utilizing woody biomass. Background Art
[0002] Conventionally, synthetic polymers such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, and polyethylene terephthalate have been used as resin compositions having excellent thermoformability. In recent years, due to increasing concern for the global environment, environmentally friendly biodegradable materials are being sought to replace these synthetic polymers.
[0003] It is known that cellulose acetate is biodegradable and decomposed by activated sludge. On the other hand, cellulose acetate has poor thermal meltability due to hydrogen bonds caused by residual hydroxyl groups in the molecular chain. Therefore, technologies for imparting thermoformability to cellulose acetate have been studied. For example, Japanese Patent Publication No. 60-155710 (Patent Document 1) discloses a yarn forming method in which modified cellulose acetate obtained by adding cyclic ester to cellulose acetate having free hydroxyl groups is melted and spun in air. Japanese Patent Publication No. 6-207045 (Patent Document 2) discloses a thermoplastic cellulose derivative obtained by kneading and reacting a polyacid or its anhydride with a monoepoxide or a polyol in the presence of a cellulose derivative having unsubstituted hydroxyl groups (such as cellulose acetate).
[0004] Generally, pulp is used as a raw material in the production of cellulose acetate. In the production of pulp, for example, multiple processes such as wood crushing, cooking, washing, bleaching, and drying are required, which has a high environmental load and is a major factor in increasing costs. In addition, in order to achieve carbon neutrality and zero emissions, attention is paid to the development of materials derived from biomass resources instead of materials derived from petroleum resources. For example, as a biomass resource derived from plants, it is particularly desirable to use woody biomass that does not compete with food and does not increase carbon dioxide in the atmosphere.
[0005] The main component of woody biomass is a natural polymer mixture called lignocellulose. Lignocellulose forms a strong high-level structure of complex entanglement of cellulose, hemicellulose and lignin. In addition, cellulose forms a strong cellulose I-type crystal structure, which hinders plasticity. Therefore, it becomes a big problem to directly use woody biomass such as wood as a molding material.
[0006] For example, as a technology for acetylation of wood as it is, the following method is disclosed in Japanese Patent Publication No. 2011-510842 (Patent Document 3): commercial-sized wood is immersed in an acetylation solution in a pressure reaction vessel and acetylated by heating in two stages under controlled conditions. Rowell MR et al. (2014) Acetylation of Wood, in Deterioration and Protection of Sustainable Biomaterials, Chapter 18, pp301-327 (Non-Patent Document 1) describes a non-uniform acetylation method for acetylation of wood. Yabune H. (1997) Cellulose Commun., Vol. 4, No. 3, pp114-122 (Non-Patent Document 2) describes a method for preparing cellulose diacetate using low-α cellulose as a raw material with a focus on global environmental protection.
[0007] In addition, as a technology for modifying wood without pulping, Japanese Patent Laid-Open No. 5-39412 (Patent Document 4) discloses a degradable resin composition containing a mixture of an etherified or esterified lignocellulose modification (e.g., benzyl etherified wood powder) and a fatty acid polyester (e.g., polycaprolactone). Japanese Patent Laid-Open No. 7-304897 (Patent Document 5) discloses a thermoplastic chemically modified lignocellulose composition obtained by reacting a polyacid or its anhydride with a monoepoxide or a polyol in the presence of a chemically modified lignocellulose having unsubstituted hydroxyl groups (e.g., acetylated lignocellulose).
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 60-155710
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 6-207045
[0012] Patent Document 3: Japanese Patent Application No. 2011-510842
[0013] Patent Document 4: Japanese Patent Application Laid-Open No. 5-39412
[0014] Patent Document 5: Japanese Patent Application Laid-Open No. 7-304897
[0015] Non-patent literature
[0016] Non-patent document 1: Rowell MR et al. (2014) Acetylation of Wood, in Deterioration and Protection of Sustainable Biomaterials, Chapter 18, pp301-327 Non-patent document 2: Yabune H. (1997) Cellulose Commun. Vol. 4, No. 3, pp114-122 Summary of the invention
[0017] Problems to be solved by the invention
[0018] The technologies disclosed in Patent Document 3 and Non-Patent Documents 1-2 are not technologies that aim at thermoformable compositions. The compositions disclosed in Patent Documents 4-5 are not thermoplastic compositions that can replace the materials derived from petroleum resources that have been used in the past. In addition, according to the knowledge of the inventors of the present disclosure, the physical properties of the molded products obtained by thermoforming the compositions disclosed in Patent Documents 4-5 also have room for further improvement.
[0019] The object of the present disclosure is to provide a composition that can produce a molded product having excellent thermoplasticity and excellent mechanical properties. From another perspective, the object of the present disclosure is to provide a method for producing a composition that uses woody biomass and has a low environmental load. In particular, the object of the present disclosure is to provide a composition suitable for thermoforming and a method for producing the composition.
[0020] Solutions for solving problems
[0021] As a result of intensive studies, the inventors of the present disclosure have focused on the fact that catalyst residues in a thermoplastic composition are one of the main factors for quality deterioration during thermoforming, and have thus arrived at the configuration of the present disclosure.
[0022] That is, the composition of the present disclosure contains acetylated wood powder, and the acetylated wood powder does not substantially contain inorganic acid esters bonded to the cellulose skeleton.
[0023] The method for producing the composition disclosed herein comprises: (1) subjecting wood powder to a decompression treatment; (2) subjecting the decompression-treated wood powder to a pressurization treatment at an absolute pressure of 10 bar or more while immersing the decompression-treated wood powder in a solvent containing an acetylating agent; and (3) after the pressurization treatment, subjecting the wood powder and the solvent containing the acetylating agent to an acetylation treatment under an inert gas atmosphere at a pressurization state of an absolute pressure of 1.1 to 1.9 bar and maintaining a temperature of 60 to 130° C.
[0024] Effects of the Invention
[0025] The composition disclosed herein includes acetylated wood powder produced without using a conventional acetylation catalyst. The composition has the same degree of thermoplasticity as conventional molding materials derived from petroleum resources, and does not produce quality degradation due to catalyst residues during thermoforming. The molded product obtained from the composition has excellent quality such as mechanical properties. The composition disclosed herein is suitable for use as a thermoforming composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a photograph of the appearance of the molded product (film) of Example 7.
[0027] Figure 2 This is a photograph of the appearance of the molded product (film) of Example 6.
[0028] Figure 3 This is a photograph of the appearance of the molded product (film) of Example 5.
[0029] Figure 4 This is a photograph of the appearance of the molded product (film) of Example 4.
[0030] Figure 5 This is a photograph of the appearance of the molded product (film) of Example 3.
[0031] Figure 6 This is another photograph of the appearance of the molded product (film) of Example 3.
[0032] Figure 7 This is a scanning electron microscope (SEM) image of the fracture surface after the tensile test of Example 3 (magnification 5000 times).
[0033] Figure 8 This is a photograph of the appearance of the molded product (film) of Comparative Example 2.
[0034] Fig. 9 This is a SEM image of the fracture surface after the tensile test of Comparative Example 2 (magnification 5000 times).
[0035] Fig.10 It is another appearance photograph of the molded product (film) of Example 3 (upper figure), and it is an appearance photograph of the molded product (film) of Example 3 when it is placed on a paper with text (lower figure).
[0036] Fig.11 It is a photograph of the appearance of the molded product (film) of Example 4 (upper figure), and it is a photograph of the appearance when the molded product (film) of Example 4 is placed on a paper with text (lower figure).
[0037] Fig.12 It is a photograph of the appearance of the molded product (film) of Example 5 (upper figure), and it is a photograph of the appearance when the molded product (film) of Example 5 is placed on a paper with text (lower figure).
[0038] Fig.13 It is a photograph of the appearance of the molded product (film) of Example 6 (upper figure), and it is a photograph of the appearance when the molded product (film) of Example 6 is placed on a paper with text (lower figure).
[0039] Fig.14 It is a photograph of the appearance of the molded product (film) of Example 7 (upper figure), and it is a photograph of the appearance when the molded product (film) of Example 7 is placed on a paper with text (lower figure). DETAILED DESCRIPTION
[0040] Hereinafter, an example of a preferred embodiment is specifically described. Each configuration and combination thereof in each embodiment is an example, and the addition, omission, substitution and other changes of the configuration may be appropriately made without departing from the main purpose of the present disclosure. The present disclosure is not limited to the embodiment but only to the technical solution. In addition, each scheme disclosed in this specification may also be combined with any other feature disclosed in this specification.
[0041] It should be noted that in the present specification, "X to Y" indicating a range means "above X and below Y", and "ppm" means "ppm by mass". "Mass %" and "weight %" are used as synonyms. In addition, unless otherwise noted, the test temperature is room temperature (20°C ± 5°C).
[0042] [Composition]
[0043] The composition disclosed in the present invention contains acetylated wood powder. As described later, there is no need to add an acetylation catalyst in the manufacture of the composition. That is, in the composition, the acetylated wood powder does not substantially contain catalyst residues. The composition is preferably substantially composed only of acetylated wood powder. The composition has the same degree of thermoplasticity as conventional molding materials derived from petroleum resources. Moreover, during the thermoforming of the composition, the quality degradation caused by catalyst residues can be avoided. According to the composition disclosed in the present invention, a molded product of excellent quality can be provided by conventional thermoforming technology. The composition disclosed in the present invention particularly has physical properties suitable for thermoforming.
[0044] Hereinafter, in this specification, the composition and the method for producing the composition are described. In particular, as a representative and preferred embodiment of the composition, a thermoforming composition is described. In addition, as a representative and preferred embodiment of the composition, a method for producing the thermoforming composition is described. In this specification, the composition is not limited to the thermoforming composition, and the method for producing the composition is not limited to the method for producing the thermoforming composition.
[0045] [Thermoforming composition]
[0046] As a preferred example of the present disclosure, a thermoforming composition contains acetylated wood powder. As described later, there is no need to add an acetylation catalyst in the manufacture of the thermoforming composition. That is, in the thermoforming composition, the acetylated wood powder does not substantially contain catalyst residues. The thermoforming composition is preferably substantially composed of only acetylated wood powder. The thermoforming composition has the same degree of thermoplasticity as conventional molding materials derived from petroleum resources. Moreover, during thermoforming of the thermoforming composition, quality degradation caused by catalyst residues can be avoided. According to the thermoforming composition, a molded product of excellent quality can be provided by conventional thermoforming technology.
[0047] Here, "thermoforming" means that a thermoplastic composition is heated to soften it, and then an external force is applied to deform it by compressed air, vacuum, mold, hot plate, plug, etc., and then cooled to form it into an arbitrary shape. In addition, "acetylated wood powder" refers to wood powder that has been acetylated. "Acetylation" refers to the treatment of introducing acetyl groups into wood powder. Specifically, it is defined as a chemical treatment for replacing the hydrogen atoms of a part of the hydroxyl groups (-OH) in the wood powder with acetyl groups (-CO-CH3). Here, "wood powder" refers to the whole wood powder that is fragmented by chopping and / or crushing the wood biomass as a raw material. "Wood powder as a whole" means that the fragmented wood powder has not been separated or graded into components such as lignin, hemicellulose, and cellulose.
[0048] In addition, in the present disclosure, "catalyst residue" is a component generally derived from a catalyst used in an acetylation treatment (hereinafter sometimes referred to as an acetylation catalyst), and is a concept that includes not only the catalyst itself, but also a substance that is ester-bonded to a cellulose skeleton in the course of an acetylation reaction. For example, when wood powder is acetylated using an inorganic acid as an acetylation catalyst, the inorganic acid reacts with the hydroxyl groups of the cellulose skeleton. As described later, the acetylated wood powder of the present disclosure is not manufactured using an acetylation catalyst, so the acetylated wood powder does not substantially contain an inorganic acid ester bonded to a cellulose skeleton. It should be noted that "substantially free of" means that it does not contain an inorganic acid ester generated by the reaction of a catalyst intentionally added in the acetylation treatment of the wood powder, but sometimes the same component contained in the wood powder itself will be detected as an inorganic acid ester. Therefore, as long as the detected amount of the inorganic acid ester detected from the composition is less than 0.5% by weight, preferably less than 0.3% by weight, and more preferably less than 0.2% by weight relative to the entire composition, it is included in the technical scope of the present disclosure. The detected amount of the inorganic acid ester is preferably 0% by weight relative to the entire composition. The detected amount of the inorganic acid ester can be 0% by weight or more and 0.5% by weight or less, 0% by weight or more and 0.3% by weight or less, or 0% by weight or more and 0.2% by weight or less relative to the entire composition. It should be noted that the quantification of the inorganic acid ester in the composition can be carried out using a known detection method (e.g., a method of performing elemental analysis on the gas generated by a combustion method, etc.). In addition, when the composition is substantially composed of acetylated wood powder only, it is preferred that the detected amount of the inorganic acid ester detected from the acetylated wood powder satisfies the above range relative to the entire acetylated wood powder.
[0049] For example, if a sulfuric acid catalyst as an acetylation catalyst is used as an example, the inorganic acid ester refers to a bonded sulfuric acid component. As the bonded sulfuric acid component, more specifically, sulfuric acid is bonded to the wood cellulose constituting the wood powder in the form of a sulfuric acid group or a sulfonic acid group, and the like. That is, the acetylated wood powder of the present disclosure does not substantially contain a sulfuric acid ester (bonded sulfuric acid) derived from the catalyst. In this case, the amount of inorganic acid ester (sulfuric acid ester amount) of the acetylated wood powder can be evaluated by measuring the sulfur content (including bonded sulfuric acid).
[0050] Specifically, for the sulfur content of acetylated wood powder, a dried sample was calcined in an electric furnace at 1300°C, the sublimated sulfurous acid gas was captured in 10% hydrogen peroxide, and titrated with a specified sodium hydroxide aqueous solution. The SO4 2- The conversion amount is calculated as SO4 in 1g of the sample in an absolutely dry state. 2-The amount is expressed in ppm. The sulfur content of the acetylated wood powder of the present invention measured by this method can be less than 100 ppm, can be less than 80 ppm, or can be less than 50 ppm. It should be noted that the sulfur contained in the wood powder itself is almost all sulfur-containing protein. Since the sulfur-containing protein is almost completely decomposed before reaching 600°C, the temperature of the above-mentioned electric furnace can also be set to 600°C to conduct the same test to estimate the amount of sulfur derived from the wood. The sulfur content of the acetylated wood powder is preferably 0 ppm. The sulfur content of the acetylated wood powder can be greater than 0 ppm and less than 100 ppm, can be greater than 0 ppm and less than 80 ppm, or can be greater than 0 ppm and less than 50 ppm.
[0051] In the thermoforming composition disclosed herein, the amount of acetyl groups introduced into the acetylated wood powder affects thermoplasticity. The amount of acetyl groups introduced can be evaluated using the acetylation degree R, which is measured at 1730 to 1745 cm in the infrared absorption spectrum of the acetylated wood powder. -1 The peak intensity S1 derived from the stretching vibration of the acetyl carbonyl group at 1020-1040 cm -1 The acetylation degree R is expressed by the ratio S1 / S2 of the peak intensity S2 of the stretching vibration of CO in the cellulose skeleton. From the viewpoint of improving thermoplasticity, the acetylation degree R may be 0.50 or more, 0.55 or more, or 0.60 or more. As described later, from the viewpoint of being able to introduce a lactone-type ring-opening polymer into the acetylated wood powder, the acetylation degree R is preferably 0.90 or less.
[0052] From the viewpoint of improving thermoplasticity, the acetyl substitution degree calculated assuming that the entire amount of acetylated wood powder is cellulose acetate may be 0.9 or more, 1.0 or more, or 1.1 or more. Furthermore, from the viewpoint of being able to introduce a lactone ring-opening polymer described later, the acetyl substitution degree may be 2.9 or less, or 2.8 or less.
[0053] In the present disclosure, the shape of the acetylated wood powder is not particularly limited. From the viewpoint of easy handling, the acetylated wood powder may be in powder or granular form. The size of the powdered or granular acetylated wood powder may be 0.10 mm to 3.0 mm, 0.15 mm to 2.0 mm, 0.20 mm to 1.0 mm, 0.25 mm to 0.75 mm, or 0.30 mm to 0.50 mm. The size of the acetylated wood powder is measured by a sieving classification method using a JIS standard sieve.
[0054] The amount of acetylated wood powder contained in the thermoforming composition is not particularly limited, and can be appropriately selected within the range that can achieve the effects of the present disclosure and according to the intended use. For example, from the viewpoint of easy thermoforming and improved biodegradability, the amount of acetylated wood powder in the thermoforming composition can be 60% by weight or more, 70% by weight or more, 80% by weight or more, or 90% by weight or more, and the upper limit is 100% by weight.
[0055] In one embodiment, a lactone ring-opening polymer (hereinafter sometimes referred to as polylactone) is grafted to the acetylated wood powder contained in the thermoforming composition. Here, "lactone" refers to a cyclic compound having an ester group (-COO-) in the molecule, and refers to a compound having an ester bond in the molecule obtained by removing water from a carboxyl group (-COOH) and a hydroxyl group (-OH) in the same molecule. In this specification, lactones used for ring-opening polymerization are sometimes referred to as "lactone monomers".
[0056] A thermoforming composition comprising acetylated wood powder grafted with polylactone (hereinafter sometimes referred to as polylactone-modified acetylated wood powder) has better thermoplasticity. By thermoforming the composition, a molded product with excellent transparency and tensile properties can be obtained. Acetylated wood powder grafted with aliphatic polylactone is preferred from the viewpoint of being biodegradable and having a small load on the environment.
[0057] The amount of the polylactone-modified acetylated wood powder contained in the thermoforming composition is not particularly limited. From the viewpoint of facilitating thermoforming and improving the transparency of the obtained molded product, the amount of the polylactone-modified acetylated wood powder in the thermoforming composition may be 60% by weight or more, 70% by weight or more, 80% by weight or more, or 90% by weight or more, and the upper limit is 100% by weight.
[0058] The acetylated wood powder grafted with polylactone can be obtained by ring-opening graft polymerization of unsubstituted hydroxyl groups in the acetylated wood powder with lactones, or by chemically bonding a ring-opening polymer of lactones to unsubstituted hydroxyl groups in the acetylated wood powder. The thermoforming composition may also contain acetylated wood powder without polylactone grafted thereto within the range in which the effects of the present disclosure can be obtained.
[0059] As long as the effects of the present disclosure can be obtained, the type of lactone is not particularly limited. As lactones that can be graft-polymerized with the hydroxyl group in the acetylated wood powder, lactones having 3 to 10 carbon atoms constituting the ring can be cited. Specifically, examples include: ε-caprolactone, β-propiolactone, γ-butyrolactone, δ-valerolactone, etc. It is also possible to use one or a combination of two or more lactones.
[0060] From the viewpoint of high polymerization reactivity, ε-caprolactones are preferred. Examples of ε-caprolactones include ε-caprolactone, monomethyl-ε-caprolactone, monoethyl-ε-caprolactone, monodecyl-ε-caprolactone, monopropyl-ε-caprolactone, dimethyl-ε-caprolactone, trimethyl-ε-caprolactone, ethoxy-ε-caprolactone, and cyclohexyl-ε-caprolactone.
[0061] The preferred lactone is ε-caprolactone from the viewpoint of low cost and easy availability. The composition comprising acetylated wood powder grafted with a ring-opening polymer of ε-caprolactone is easy to thermoform, and the obtained molded article has improved transparency and tensile properties and exhibits good biodegradability.
[0062] In the acetylated wood powder grafted with polylactone, the content of polylactone is not particularly limited. From the viewpoint of improving thermoplasticity, the content of polylactone is preferably 3% by weight or more, more preferably 5% by weight or more, and further preferably 7% by weight or more relative to the entire polylactone-modified acetylated wood powder. From the viewpoint of easy manufacturing, the content of polylactone is preferably 30% by weight or less, more preferably 25% by weight or less, and further preferably 20% by weight or less. The content of polylactone grafted to the acetylated wood powder can be calculated, for example, based on the weight change before and after grafting. The content of polylactone can also be calculated based on the weight change before and after the hydrolysis treatment of the polylactone-modified acetylated wood powder.
[0063] In the acetylated wood powder grafted with polylactone, the average degree of polymerization of the lactone ring-opening polymer is not particularly limited. From the viewpoint of improving the transparency and tensile properties of the obtained molded article, the average degree of polymerization may be 2.0 or more, 5.0 or more, 10.0 or more, 15.0 or more, or 20.0 or more. From the viewpoint of reflecting the physical properties of the acetylated wood powder, the average degree of polymerization may be 100 or less. The average degree of polymerization of the polylactone in the polylactone-modified acetylated wood powder is calculated based on the acetyl substitution degree and the polylactone content.
[0064] In the present disclosure, the shape of the polylactone-modified acetylated wood powder is not particularly limited. For example, the polylactone-modified acetylated wood powder may be in powder or particle form. From the viewpoint of easy thermoforming, the size of the powder or particle polylactone-modified acetylated wood powder may be 0.10 mm to 3.0 mm, 0.15 mm to 2.0 mm, 0.20 mm to 1.0 mm, 0.25 mm to 0.75 mm, or 0.30 mm to 0.50 mm. The size of the polylactone-modified acetylated wood powder is determined by a sieving and classification method using a JIS standard sieve.
[0065] [Method for producing thermoforming composition]
[0066] The method for producing the thermoforming composition comprises: (1) subjecting wood powder to a decompression treatment; (2) subjecting the wood powder after the decompression treatment to a pressure treatment at an absolute pressure of 10 bar or more while being immersed in a solvent containing an acetylating agent; and (3) after the pressure treatment, subjecting the wood powder and the solvent containing the acetylating agent to an acetylation treatment under an inert gas atmosphere at a pressure of 1.1 to 1.9 bar and maintaining a temperature of 60 to 130° C. The wood powder is acetylated. According to the production method disclosed in the present invention, by appropriately performing the decompression treatment and the pressure treatment, acetyl groups can be introduced into the wood powder without using an acetylation catalyst. Thus, an acetylated wood powder substantially free of catalyst residues is obtained. The acetylated wood powder can also be used as the thermoforming composition disclosed in the present invention as it is. The thermoforming composition can also contain unacetylated wood powder within the scope of obtaining the effects of the present invention.
[0067] The manufacturing method may also include: (4-1) adding lactones to the acetylated wood powder for graft polymerization, or (4-2) adding a ring-opening polymer of lactones to the acetylated wood powder for grafting reaction. Thus, polylactone-modified acetylated wood powder is obtained. The polylactone-modified acetylated wood powder can also be used as the thermoforming composition of the present invention as it is. Within the scope of the effect of the present invention, the thermoforming composition may contain acetylated wood powder that has not been modified with polylactone, and may also contain wood powder that has not been acetylated. It is preferred to use the manufacturing method (4-1) of adding lactones to the acetylated wood powder for graft polymerization, which has high reaction efficiency.
[0068] Wood powder as a raw material can be obtained, for example, by chopping or crushing woody biomass. The woody biomass is not particularly limited, and broadleaf trees, coniferous trees, etc. can be used. Thinning materials, lumber waste, woodland residual materials, etc. produced in the forestry field can be used. If necessary, herbaceous biomass such as straw, bamboo, and wheat bran can also be used in combination.
[0069] The shape and size of the wood powder are not particularly limited. For example, when the wood powder is crushed into a powder or particle form, the size of the wood powder can be 0.10 mm to 3.0 mm, 0.15 mm to 2.0 mm, 0.20 mm to 1.0 mm, 0.25 mm to 0.75 mm, or 0.30 mm to 0.50 mm from the viewpoint of improving the reaction efficiency. The size of the wood powder is measured by a sieving classification method using a JIS standard sieve.
[0070] In the manufacturing method disclosed herein, there is no particular limitation on the mechanism for the decompression treatment and the pressurization treatment. For example, known mechanisms such as an aspirator, an ejector, a compressor, and a mechanical pump can be used to adjust the pressure to the preferred pressure range described later. It should be noted that in this specification, when indicating pressure, "absolute pressure" using an absolute vacuum reference (0 bar) is used unless otherwise specified.
[0071] The reduced pressure treatment of the wood powder before the acetylation treatment is carried out under a reduced pressure state with an absolute pressure of preferably 0.2 bar or less, more preferably 0.1 to 0.2 bar. By this reduced pressure treatment, the water content in the wood powder, which is the main factor hindering the acetylation reaction described later, is reduced. From the viewpoint of promoting the acetylation treatment, the water content of the wood powder after the reduced pressure treatment is preferably 10% by weight or less, more preferably 8% by weight or less, and further preferably 5% by weight or less. The reduced pressure treatment temperature is usually room temperature and can be 20 to 30°C. The reduced pressure treatment time is not particularly limited and can be appropriately selected within the range that can obtain the desired water content.
[0072] In this manufacturing method, the wood powder after the decompression treatment is subjected to pressure treatment while being immersed in a solvent containing an acetylating agent. A conventionally known acetylating agent and solvent can be appropriately selected and used. As the acetylating agent, acetic anhydride, acetic acid halide, etc. can be exemplified. In addition, as the solvent, acetic acid, dichloromethane, etc. can be cited. Two or more solvents can also be used in combination. It is preferred to use a combination of acetic anhydride as the acetylating agent and acetic acid as the solvent.
[0073] The mixing ratio of the acetylating agent to the solvent is not particularly limited and can be appropriately selected according to the types of the acetylating agent and the solvent. For example, the weight ratio of the acetylating agent to the solvent (acetylating agent / solvent) can be 50 / 50 or more, 60 / 40 or more, or 70 / 30 or more. In addition, it can be 95 / 5 or less, or 90 / 10 or less.
[0074] The amount of the acetylating agent used can be appropriately selected according to the amount of acetyl groups introduced into the acetylated wood powder. For example, the amount of the acetylating agent used can be 200 parts by weight or more, 210 parts by weight or more, 400 parts by weight or less, or 350 parts by weight or less, relative to 100 parts by weight of the wood powder as a raw material. The amount of the solvent used can be 10 parts by weight or more, 20 parts by weight or more, 400 parts by weight or less, or 350 parts by weight or less, relative to 100 parts by weight of the wood powder as a raw material.
[0075] When the wood powder is subjected to pressure treatment while immersed in a solvent containing an acetylating agent, an inert gas is introduced into the reaction system, and the process is carried out under a pressure of preferably 10 bar or more, more preferably 10 to 20 bar. As the inert gas, nitrogen is preferably used. Through the pressure treatment, the acetylating agent is efficiently introduced into the structure of the wood powder, and a uniform acetylation treatment can be performed. The pressure treatment temperature is usually room temperature, and can be 20 to 30°C. The pressure treatment time is not particularly limited and can be appropriately selected according to the treatment amount of the wood powder and the treatment temperature.
[0076] In this manufacturing method, wood powder and a solvent containing an acetylating agent are pressurized at 10 bar or more, then the pressure is reduced to an absolute pressure of 1.1 to 1.9 bar, and the mixture is heated to a temperature of 60 to 130° C. in an inert gas atmosphere at a pressurized state of 1.1 to 1.9 bar. The acetylation reaction proceeds by heating. Specifically, acetyl groups are introduced into hydroxyl groups in the wood cellulose constituting the wood powder to obtain acetylated wood powder. The heating time can be appropriately selected according to the amount of acetyl groups introduced. As the inert gas, the nitrogen gas described above is preferably used.
[0077] As long as the effects of the present disclosure can be obtained, the acetylation treatment can be carried out in one stage or in two stages. In the case of a one-stage treatment, for example, it can be carried out at 130°C for more than 90 minutes. In the case of a two-stage treatment, for example, it can be heated at 60°C for 45 minutes (first acetylation), then heated to 130°C over 10 minutes, and heated at 130°C for 35 minutes (second acetylation).
[0078] In this manufacturing method, the wood powder after acetylation can be washed to remove excess acetylating agent and solvent, or the wood powder after acetylation can be provided for graft polymerization with lactones described later without washing. In the acetylation, the acetylating agent (e.g., acetic anhydride) reacts with water in the reaction system. Through this reaction, water is removed from the reaction system. In this reaction system, when the residual hydroxyl groups contained in the acetylated wood powder are used as initiators to carry out graft polymerization with lactones, the side reaction of water as an initiator is suppressed. Thus, a graft polymer with little (or no) mixing of homopolymers of lactones as by-products can be obtained. It should be noted that, in the case of washing the wood powder after acetylation, the type of washing solvent is not particularly limited, and a solvent that can dissolve the acetylating agent and solvent can be appropriately selected. When acetic anhydride is used as the acetylating agent and acetic acid is used as the solvent, the preferred washing solvent is water.
[0079] In this manufacturing method, the washed acetylated wood powder may be dried. The weight increase rate (%) calculated based on the weight of the dried acetylated wood powder and the weight of the wood powder before the reduced pressure treatment is an indicator of the amount of acetyl groups introduced into the wood powder. From the viewpoint of easy thermoforming, the weight increase rate of the acetylated wood powder obtained after drying at 105°C for 12 hours is preferably 20.0% by weight or more, more preferably 22.0% by weight or more, and further preferably 24.0% by weight or more. There is no particular upper limit, but from the viewpoint of introducing polylactone by graft polymerization, the weight increase rate is preferably 90.0% by weight or less.
[0080] When a lactone is added to the acetylated wood powder for graft polymerization, the lactones mentioned above can be used, preferably ε-caprolactones, and more preferably ε-caprolactone.
[0081] The average degree of polymerization of the polycaprolactone grafted to the acetylated wood powder can be controlled by the ratio of the acetylated wood powder to the lactones. In the polycaprolactone-modified acetylated wood powder, from the viewpoint of reflecting the physical properties of the polycaprolactone, the ratio of the acetylated wood powder to the lactones can be 1:2 or more, 1:5 or more, 1:10 or more, 1:15 or more, 1:20 or more, or 1:40 or more in terms of acetylated wood powder:lactones (weight ratio). That is, in the polycaprolactone-modified acetylated wood powder, the lactones can be 200 parts by weight or more, 500 parts by weight or more, 1000 parts by weight or more, 1500 parts by weight or more, 2000 parts by weight or more, or 4000 parts by weight or more relative to 100 parts by weight of the acetylated wood powder. In addition, in the polycaprolactone-modified acetylated wood powder, from the viewpoint of expressing the physical properties of the acetylated wood powder, the ratio of the acetylated wood powder to the lactones may be 1:200 or less in terms of acetylated wood powder:lactones (weight ratio). That is, in the polycaprolactone-modified acetylated wood powder, the lactones may be 20,000 parts by weight or less relative to 100 parts by weight of the acetylated wood powder.
[0082] When lactones are added to acetylated wood powder for graft polymerization, a polymerization catalyst is preferably used from the viewpoint of improving reaction efficiency. Examples of the polymerization catalyst include diphenyl phosphate, 2-ethylhexanoic acid tin (II), methanesulfonic acid, and the like. The amount of the polymerization catalyst added is not particularly limited, and for example, the amount relative to the total amount of the acetylated wood powder and the lactones may be 0.1% by weight or more, 0.2% by weight or more, 5.0% by weight or less, or 4.0% by weight or less.
[0083] When lactones are added to acetylated wood powder for graft polymerization, the polymerization temperature may be 20° C. or higher, 50° C. or higher, 70° C. or higher, 90° C. or higher, or 140° C. or lower. The polymerization time may be selected according to the polymerization temperature to obtain a desired yield.
[0084] After the polymerization reaction is completed, in order to remove unreacted monomers and ungrafted homopolymers, the reaction product can be cleaned and / or purified. The cleaning method and purification method are not particularly limited, and known cleaning methods and purification methods can be appropriately selected and used. For example, the reaction product can be cleaned with a good solvent for lactones and polylactones, and solid separation can be performed to obtain polylactone-modified acetylated wood powder. The obtained polylactone-modified acetylated wood powder can be dried in a known manner.
[0085] The thermoforming composition may contain known additives such as plasticizers, colorants, ultraviolet absorbers, light stabilizers, antioxidants, heat stabilizers, optical property adjusters, fluorescent brighteners, flame retardants, lubricants, hydrolysis inhibitors, and water-repellents within a range that does not hinder the effects of the present invention.
[0086] [Molding products]
[0087] The molded article of the present invention can be obtained by thermoforming the thermoforming composition. The method for thermoforming the composition of the present invention is not particularly limited. Known methods such as melt molding, injection molding, and melt film forming can be used. In addition, the shape and physical properties of the molded article obtained by using the composition of the present invention as a molding material are not particularly limited. Through the acetylation degree of wood powder and the grafting amount of lactones, it can be formed into a desired shape whose transparency, strength, elastic modulus, etc. are controlled as required.
[0088] [use]
[0089] The thermoforming composition disclosed herein can be preferably used as a material for, for example, tableware, packaging containers, trays, agricultural materials, fishery materials, office automation (OA) parts, building materials, medical parts, home appliance parts, automotive components, daily groceries, stationery, eyeglass frames, etc. The thermoforming composition disclosed herein can also be applied to biodegradable mulch films in the agricultural field.
[0090] Example
[0091] The effects of the present disclosure will be clarified below by way of examples, but the present disclosure should not be interpreted restrictively based on the description of the examples. In addition, all pressures are absolute pressures.
[0092] (Test 1: Preparation and physical properties of acetylated wood flour (AW))
[0093] [Example 1]
[0094] 1.5 g of air-dried fir wood powder (passing 150 μm) was put into a reaction container and the pressure was reduced to 0.1-0.2 bar at room temperature. After 30 minutes, 10 g of an acetylating agent consisting of 90% by mass acetic anhydride (manufactured by FUJIFILM Wako Chemicals (co., Ltd.) and 10% by mass acetic acid (manufactured by FUJIFILM Wako Chemicals (co., Ltd.)) was added to the reaction container, the pressure in the container was adjusted to 10 bar, and the mixture was allowed to stand for 90 minutes. Next, after the pressure in the reaction container was reduced to 1.1-1.9 bar, the acetylation reaction was carried out in two stages under a nitrogen atmosphere. Specifically, after heating at a temperature of 60°C for 45 minutes in a pressurized state of 1.1-1.9 bar (first acetylation reaction), the temperature was raised to 130°C over 10 minutes, and the mixture was heated at a temperature of 130°C for 35 minutes (second acetylation reaction). The total heating time was 90 minutes. The obtained product was collected, washed with water, dried with air at 105° C. for 12 hours, and then vacuum dried at 105° C. for 24 hours, thereby obtaining the acetylated wood powder of Example 1.
[0095] [Example 2]
[0096] Acetylated wood powder of Example 2 was obtained in the same manner as in Example 1 except that the acetylation reaction was carried out in one step (130° C. / 90 minutes).
[0097] [Comparative Example 1]
[0098] The air-dried fir wood powder (passage 150 μm) used in Examples 1 and 2 was used as Comparative Example 1.
[0099] [Crystallinity CI]
[0100] Wide-angle X-ray diffraction measurement was performed to determine the crystallinity CI (%) of Examples 1-2 and Comparative Example 1. The results obtained are shown in Table 1 below. A sample horizontal multifunctional X-ray diffraction apparatus (trade name "Ultima-IV") manufactured by RIGAKU Co., Ltd. was used for the measurement. The measurement was performed at room temperature (about 25°C). Other measurement conditions are as follows.
[0101] Radiation source:
[0102] Sampling rate: 1° / min.
[0103] Sampling width: 0.02°.
[0104] Tube current: 40mA.
[0105] Measuring range: 2θ = 2-40°.
[0106] Number of repetitions: 1 time.
[0107] Tube voltage: 40kV.
[0108] Optical system: parallel beam method.
[0109] [Degree of acetylation R]
[0110] Using a Shimadzu Fourier transform infrared spectrophotometer (trade name "IRPrestage-21") manufactured by Shimadzu Corporation, infrared absorption spectra of the acetylated wood powders of Example 1-2 and Comparative Example 1 were obtained. The measurement conditions are as follows.
[0111] Determination method: ATR method.
[0112] Cumulative number of times: 64 times.
[0113] Measurement wavelength: 400-4000cm -1 .
[0114] Resolution: 4cm -1 .
[0115] The infrared absorption spectrum obtained was used to determine the wavelengths of 1730-1745 cm -1 The peak intensity S1 derived from the stretching vibration of the acetyl carbonyl group at 1020-1040 cm -1 The ratio S1 / S2 of the peak intensity S2 derived from the stretching vibration of CO in the cellulose skeleton at the position was taken as the acetylation degree R. The obtained results are shown in the following Table 1. From Table 1, it was confirmed that the acetylation degree R of the acetylated wood powder of Example 1-2 was increased compared with the untreated wood powder of Comparative Example 1.
[0116] [Weight gain rate WPG]
[0117] The weight W0 (g) of the wood powder before the reduced pressure treatment and the weight W1 (g) of the acetylated wood powder after drying were accurately weighed, and the weight increase rate WPG (%) was calculated by the following formula. The obtained results are shown in Table 1 below.
[0118] Weight gain rate WPG (%) = {(W1-W0) / W0}*100
[0119] [Table 1]
[0120] (Table 1)
[0121]
[0122] (Test 2: Ring-opening graft polymerization of ε-caprolactone)
[0123] [Examples 3-7]
[0124] Acetylated wood powder grafted with polycaprolactone (ACW-g-PCL) was produced using a parallel synthesis apparatus manufactured by Tokyo Rikaki Co., Ltd. (trade name: "Chem Station PPM-5512").
[0125] Five reaction tubes were prepared, and 0.1 g of the acetylated wood powder of Example 1 as a reaction raw material was added to each tube. Then, ε-caprolactone (manufactured by Daicel Co., Ltd.) was added to each reaction tube so as to achieve the ratio shown in Table 2 below, and after stirring at a temperature of 120° C. for 1 hour, a diphenylphosphoric acid / toluene solution was added. The amount of diphenylphosphoric acid (manufactured by Tokyo Chemical Industry Co., Ltd.) added was 2% by mass relative to the total amount of acetylated wood powder and ε-caprolactone.
[0126] After reacting at 120°C for 24 hours under a nitrogen stream, the mixture was cooled to 40°C and diluted by adding acetone (manufactured by Nacalai Tesque Co., Ltd.) (dilution ratio 4 to 5 times). Next, the diluted reaction solution was added dropwise to a mixed solvent of 425 ml of acetone (manufactured by Nacalai Tesque Co., Ltd.) and 25 ml of toluene (manufactured by Nacalai Tesque Co., Ltd.), stirred overnight, and solid components were separated by decantation and vacuum filtration (0.2 μm polytetrafluoroethylene (PTFE) membrane filter). The obtained solid components were placed in methanol (manufactured by Nacalai Tesque Co., Ltd.) and filtered and collected. This operation was repeated twice for washing to remove polycaprolactone homopolymers, and dried at 40°C for 12 hours with air blowing, and then vacuum dried at 40°C for 48 hours to obtain acetylated wood powder grafted with polycaprolactone.
[0127] The weight of the dried polycaprolactone grafted-acetylated wood powder was accurately weighed, and the reaction yield (%) was calculated as a ratio to the total weight of the acetylated wood powder and ε-caprolactone before grafting. The obtained results are shown in Table 2 below. Table 2 confirmed that the yield of the grafting reaction was improved by using acetylated wood powder as a reaction raw material.
[0128] Assuming that the wood is entirely cellulose and the weight increase rate (24.5%) of Example 1 is based on the acetylation reaction, the acetyl substitution degree of the acetylated wood powder of Example 1 is calculated to be 0.945. Based on the acetyl substitution degree and the reaction yield, the number of caprolactone units bonded to each residual hydroxyl group of the acetylated wood was calculated. The obtained results are shown in the following Table 2 as the average degree of polymerization.
[0129] [Comparative Examples 2-6]
[0130] Comparative Examples 2, 4 and 6 were obtained in the same manner as in Examples 3 to 7 except that the acetylated wood powder of Example 1 was changed to the wood powder of Comparative Example 1, and the ratio of ε-caprolactone to the reaction raw material was set to the ratio shown in Table 2 below. In Comparative Examples 3 and 5, cellulose acetate (manufactured by Daicel Corporation, acetyl substitution degree 2.15) was used as the reaction raw material. The reaction yields of each are shown in Table 2 below.
[0131] [Film forming]
[0132] The polycaprolactone grafted-acetylated wood powder of Examples 3-7 and the polycaprolactone grafted-wood powder of Comparative Example 2 were hot-pressed using a 10-ton table-top hot press (manufactured by Toyo Seiki Co., Ltd.). Specifically, a polyethylene terephthalate (PET) sheet was placed on a metal plate, and about 0.3 g of polycaprolactone grafted-acetylated wood powder or polycaprolactone grafted-wood powder was placed in the center of the PET sheet as a sample. The PET sheet and the metal plate were further placed on the sample in sequence, and then sandwiched between hot press hot plates adjusted to 150° C., and slowly pressurized to a gauge pressure of 5 MPa over 2 minutes, pressurized at 5 MPa for 30 seconds, exhausted, and then the pressure was suddenly raised to 15 MPa, and the pressure was maintained at this state for 30 seconds. After the pressure was released, a second hot press was immediately used to cold-press at the same pressure (15 MPa) at room temperature for about 3 minutes to obtain a film-like molded product. Furthermore, the obtained film-like molded product was placed on a paper surface having text written thereon, and the transparency of the film was visually confirmed.
[0133] According to Examples 3-7, uniform and flexible films were formed by hot press molding using a hot press. On the other hand, the film obtained using Comparative Example 2 was very brittle and could not be used to prepare a test piece for the tensile test described later. The appearance photographs of the films obtained using Example 3 and Comparative Example 2 are shown in FIG. Figure 6 and Figure 8 . Fig.10 2 shows another appearance photograph of the film obtained using Example 3 (upper figure) and an appearance photograph of the film placed on a paper with text written thereon in order to confirm the transparency of the film (lower figure). Figure 11-14 The photographs of the appearance of the films obtained using Examples 4 to 7 (upper figure) and the photographs of the appearance when the films were placed on a paper with text written thereon in order to confirm the transparency of each film (lower figure) are shown.
[0134] [Table 2]
[0135] (Table 2)
[0136]
[0137]
[0138] [Haze measurement]
[0139] The haze meter (trade name "Haze Meter NDH4000" manufactured by Nippon Denshoku Industries Co., Ltd.) was used to measure the turbidity of the film having a thickness of about 0.1 mm obtained by the above method. The measurement results are shown in Table 3 below. The appearance photograph of the test piece used for the measurement is shown in Figure 1-5 From Tables 2 and 3 and the appearance photographs, it was confirmed that the higher the average degree of polymerization of polycaprolactone, the smaller the haze and the higher the transparency of the obtained film.
[0140] [Tensile test]
[0141] A dumbbell-shaped test piece was made from a film having a thickness of about 0.1 mm obtained by the method using a test piece punching blade No. 7 die (manufactured by Polymer Metering Co., Ltd.) in accordance with JIS K 6251. The width and thickness were measured at three locations between the markings of each test piece using a vernier caliper and a micrometer, and the cross-sectional area was calculated using the average value. Then, a tensile tester (trade name "AUTOGRAPH AGS-5kNX" manufactured by Shimadzu Corporation) was used to perform a tensile test on each test piece to determine the load-deformation curve. In data analysis, the company's software "TRAPEZIUM X" was used to determine the tensile strength (MPa), Young's modulus (MPa), and elongation at break (%). The measurement conditions were as follows. The results obtained in Examples 3-7 and Comparative Example 2 are shown in Table 3 below.
[0142] Span length: 15mm.
[0143] Crosshead speed: 5mm / min.
[0144] [Table 3]
[0145] (Table 3)
[0146]
[0147]
[0148] Scanning microscope images (magnification 5000 times) of the fracture surfaces of the films of Example 3 and Comparative Example 2 after the tensile test are shown in Figure 7 and Fig. 9 .according to Fig. 9 It was confirmed that the matrix resin was cracked in the fracture surface of the film of Comparative Example 2, and there were traces of wood powder estimated to be 80 mesh in size being pulled out of the matrix. It is speculated that in Comparative Example 2, the hydrophobic lactone monomer could not penetrate into the interior of the non-acetylated highly polar wood powder structure, so the grafting reaction occurred only near the surface of the wood powder, and therefore sufficient thermoplasticity could not be obtained.
[0149] On the other hand, Figure 7As shown, no cracks were observed in the cross section of the film of Example 3 as in Comparative Example 2. It is believed that in Example 3, the crystallinity of cellulose in the wood powder was reduced by acetylation, and the wood powder was hydrophobized, so that the lactone monomer penetrated into the interior of the acetylated wood powder structure and a grafting reaction occurred at the molecular level, so that the acetylated wood powder as a whole was converted into a homogeneous plastic-like structure. Figure 7 In the figure, the fibrous material observed in the center is presumed to be cellulose nanofibers derived from the wood powder structure. It is presumed that this is because the degree of acetylation is low, and a grafting reaction occurs from the surface of the acetylated wood powder with the remaining wood powder structure to the inside, leaving fibrous material derived from the wood powder structure in the center. This fibrous material may contribute to the reinforcement of molded products such as films.
[0150] As described above, according to the present disclosure, a composition that uses wood biomass as a raw material and can be thermoformed can be obtained. Furthermore, by thermoforming the composition, a molded product with good properties can be obtained. According to the evaluation results, the advantages of the present disclosure are obvious.
[0151] [Public Project]
[0152] The following items disclose preferred embodiments.
[0153] [Project 1]
[0154] A composition comprises acetylated wood powder, wherein the acetylated wood powder is substantially free of inorganic acid esters bonded to a cellulose skeleton.
[0155] [Project 2]
[0156] The composition according to item 1, wherein the composition is used for thermoforming.
[0157] [Item 3]
[0158] The composition according to item 1 or 2, wherein in the infrared absorption spectrum of the acetylated wood powder, the -1 The peak intensity S1 derived from the stretching vibration of the acetyl carbonyl group at 1020-1040 cm -1 The degree of acetylation represented by the ratio S1 / S2 of the peak intensity S2 derived from the stretching vibration of CO in the cellulose skeleton is 0.50 or more.
[0159] [Item 4]
[0160] The composition according to any one of items 1 to 3, wherein a lactone ring-opening polymer is grafted onto the acetylated wood powder.
[0161] [Item 5]
[0162] The composition according to item 4, wherein the lactone is ε-caprolactone.
[0163] [Item 6]
[0164] The composition according to item 4 or 5, wherein the average degree of polymerization of the ring-opening polymer of the lactone grafted to the acetylated wood powder is 2.0 or more.
[0165] [Item 7]
[0166] A molded article, the molded article being formed from the composition according to any one of items 1 to 6.
[0167] [Item 8]
[0168] A method for producing a composition according to any one of items 1 to 6, comprising: subjecting wood powder to a decompression treatment; subjecting the decompression-treated wood powder to a pressurization treatment at an absolute pressure of 10 bar or more while immersing the decompression-treated wood powder in a solvent containing an acetylating agent; and after the pressurization treatment, subjecting the wood powder and the solvent containing the acetylating agent to an acetylation treatment under an inert gas atmosphere at a pressurized state of an absolute pressure of 1.1 to 1.9 bar, while maintaining a temperature of 60 to 130° C.
[0169] [Item 9]
[0170] The method for producing the composition according to item 8, further comprising adding lactones to the acetylated wood powder for graft polymerization.
[0171] [Item 10]
[0172] The method for producing a composition according to item 8 or 9, wherein the acetylating agent is acetic anhydride and the solvent is acetic acid.
[0173] [Item 11]
[0174] The method for producing a composition according to any one of items 8 to 10, wherein no acetylation catalyst is used in the acetylation treatment.
[0175] [Item 12]
[0176] The method for producing a composition according to any one of items 8 to 11, wherein the pressure treatment of the wood powder after the decompression treatment is performed in an inert gas atmosphere at a pressure of 10 bar or more.
[0177] [Item 13]
[0178] The method for producing a composition according to any one of items 8 to 12, wherein the decompression treatment of the wood powder is performed in a decompression state with an absolute pressure of 0.2 bar or less.
[0179] [Item 14]
[0180] The method for producing a composition according to any one of items 8 to 13, wherein the weight ratio of the acetylating agent to the solvent (acetylating agent / solvent) is 50 / 50 to 95 / 5.
[0181] [Item 15]
[0182] The method for producing a composition according to any one of items 8 to 14, wherein the increase rate of the dry weight of the wood powder after the acetylation treatment is 20.0% or more relative to the dry weight of the wood powder before the reduced pressure treatment.
[0183] Industrial Applicability
[0184] The composition described above can be suitably used for production of various molded products using injection molding, melt molding, blow molding, and the like.
Claims
1. A composition comprising acetylated wood powder, wherein the acetylated wood powder is substantially free of inorganic acid esters bonded to a cellulose skeleton.
2. The composition according to claim 1, wherein The composition is useful for thermoforming.
3. The composition according to claim 1, wherein In the infrared absorption spectrum of the acetylated wood powder, the -1 The peak intensity S1 derived from the stretching vibration of the acetyl carbonyl group at 1020-1040 cm -1 The degree of acetylation represented by the ratio S1 / S2 of the peak intensity S2 derived from the stretching vibration of CO in the cellulose skeleton is 0.50 or more.
4. The composition according to claim 1, wherein The acetylated wood powder is grafted with a lactone ring-opening polymer.
5. The composition according to claim 4, wherein The lactone is ε-caprolactone.
6. The composition according to claim 4, wherein The average polymerization degree of the ring-opening polymer of the lactone grafted to the acetylated wood powder is 2.0 or more. 7 . A molded article, the molded article being formed from the composition according to claim 1 .
8. A method for producing the composition according to claim 1, comprising: Decompression treatment of wood powder; The wood powder after the reduced pressure treatment is immersed in a solvent containing an acetylating agent, and then subjected to a pressure treatment at an absolute pressure of 10 bar or more; as well as After the pressure treatment, the wood powder and the solvent containing the acetylating agent are placed in an inert gas atmosphere at a pressure of 1.1 to 1.9 bar absolute and maintained at a temperature of 60 to 130° C. to perform an acetylation treatment on the wood powder.
9. The method for producing a composition according to claim 8, wherein: The method also includes adding lactones to the acetylated wood powder for graft polymerization.
10. The method for producing a composition according to claim 8, wherein: The acetylating agent is acetic anhydride, and the solvent is acetic acid.
11. The method for producing a composition according to claim 8, wherein: No acetylation catalyst is used in the acetylation treatment.
12. The method for producing a composition according to claim 8, wherein: The wood powder after the decompression treatment is subjected to pressure treatment in an inert gas atmosphere at a pressure of 10 bar or more.
13. The method for producing a composition according to claim 8, wherein: The decompression treatment of the wood powder is performed in a decompression state with an absolute pressure of 0.2 bar or less.
14. The method for producing a composition according to claim 8, wherein: The weight ratio of the acetylating agent to the solvent, ie, acetylating agent / solvent, is 50 / 50 to 95 / 5.
15. The method for producing a composition according to claim 8, wherein: The increase rate of the dry weight of the wood powder after the acetylation treatment is 20.0% or more relative to the dry weight of the wood powder before the reduced pressure treatment.
Citation Information
Patent Citations
Method for forming yarn
JP1985155710A
Degradable resin composition
JP1993039412A
Thermoplastic cellulose derivative composition and its production
JP1994207045A
Thermoplastic chemically modified lignocellulose composition and its production
JP1995304897A
Method and product of acetylating wood
JP2011510842A